Museums and source communities a Routledge reader - Peers, Laura L. (Laura Lynn); Brown, Alison K. Alison Kay 1971- (Routledge, 2003)
The growth of collaboration between museums and source communities - the people from whom collections originate - is an important development in modern museum practice. This volume combines influential published research with commissioned essays on the issues, problems and lessons involved.